Implementation of Musyarakah Mutanaqishah in Refinancing and Take Over Products: A Study of Legal Aspects and Basic Provisions in Islamic Banking - Salfin Abdul Rahman Al'auf; Nana Herdiana; Yoyok Prasetyo (Zona Law And Public Administration Indonesia, 2024)
This research investigates the application of the Musyarakah Mutanaqishah Agreement in two sharia-based financing products, namely refinancing products and take over products, which are used by sharia banking institutions. This study aims to analyze how the Musyarakah Mutanaqishah Agreement is used in these two products and its impact on sharia compliance, flexibility and profits for financing holders. The research method used involves documentation analysis, interviews with sharia banking practitioners, and case studies of refinancing and take over products that have been implemented. The main advantage of Akad Musyarakah Mutanaqishah is adherence to sharia principles as it avoids interest. Customers also get the flexibility to adjust payment schedules and financing terms. Although complex, it has the potential to advance the Islamic banking industry and provide options according to Islamic principles in the changing global financial world.